Conditions and characteristics of the processes of heat transfer in junctions of thermoelectric transducers; Journal of Engineering Physics and Thermophysics; Vol. 94, iss. 5 - Atroshenko Yu. K. Yuliana Konstantinovna (2021, 2021)
Title screen